Strategic planning and management of healthcare in Saudi Arabia - Jimenez, Joan Lagmay; Jacob, Prince (International Journal Of Community Medicine And Public Health, 2020)
Strategic planning and management in healthcare ensures systematic care plan and quality delivery of care to the service users which enhanced their health and well-being. Numerous challenges are continuously born in the healthcare sector which requires careful calculation and implementation of specific strategies that can help shape it to the better. The aim of the study is to discuss strategic planning and management regarding healthcare in Saudi Arabia. This study employs an electronic research strategy, where articles were selected from platform such as Google scholar, CINAHL and other such engines by following inclusion criteria. The results obtained indicate that the different strategic planning and management in healthcare is practiced at local, national and international level by Saudi Arabia. The study shows that strategic management and planning is essential for the health sector since it involves developing changes that improve the sector.